2019
DOI: 10.1186/s12967-019-1773-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical verification of the relationship between smoking and the immune microenvironment of breast cancer

Abstract: BackgroundThe immune tumor microenvironment (iTME) is thought to affect the response to chemotherapy, and tumor-infiltrating lymphocytes (TILs) are often used as an indicator to evaluate the iTME. Smoking is involved in carcinogenesis, the relationship between smoking and the iTME of lung cancer has been reported. We hypothesized that smoking would affect the iTME of breast cancer and aimed to examine this relationship based on the amount of pre-diagnosis smoking and the subsequent effects on treatment respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…To assess the association between cigarette smoking and the development of pulmonary metastasis among breast cancer patients, we performed retrospective pan-analysis of three previously reported breast cancer cohorts 53 – 55 , 58 with smoking history that comprised a total of 1077 cancer patients. We found that current or ex-smokers have significantly higher lung metastasis incidence compared to the never-smokers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the association between cigarette smoking and the development of pulmonary metastasis among breast cancer patients, we performed retrospective pan-analysis of three previously reported breast cancer cohorts 53 – 55 , 58 with smoking history that comprised a total of 1077 cancer patients. We found that current or ex-smokers have significantly higher lung metastasis incidence compared to the never-smokers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed the importance of TILs (as an indicator of ITME) in the outcome of early stage and locally advanced breast cancers. Previous studies demonstrated, however, that ITME can be influenced by multiple factors, such as comorbidities, drugs, and smoking [47]. ITME can also be influenced during chemotherapy, and these changes could also be considered important predictive factors for the outcome of breast cancer patients [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, experiments in vivo and in vitro have shown that tobacco components increase the malignancy of breast cancer cells [3][4][5]. In addition, we have shown in clinical samples that smoking can enhance HER2 expression in breast cancer and increase tumor-in ltrating lymphocyte density in the microenvironment surrounding the cancer [16,30]. From these results, we speculate that smoking may affect DCIS during the beginning of the disease, causing it to acquire invasive ability at an early stage and resulting in IDC identi ed by biopsy at initial diagnosis.…”
Section: Discussionmentioning
confidence: 89%